Studi kapasitas masyarakat sebagai mekanisme bertahan menghadapi bencana banjir di Desa Sitiarjo, Kecamatan Sumbermanjing Wetan, Kabupaten Malang - Mohamad Mambaus Su'ud; Mashur Hasan Bisri (Jurnal Teori dan Praksis Pembelajaran IPS, 2019)
The aim of this study was to determine the capacity of communities as a mechanism to withstand floods Sitiarjo Village, District Sumbermanjing Wetan. This research is descriptive qualitative. The research phase was divided into three, i.e: (1) pre-field observation; (2) field observation; (3) data processing. The method used in data collection is FGD (Focused Group Disscusion) and in-depth interviews. The results of the study indicate that the community has a strong capacity in social, cultural, economic and government aspects in dealing with floods. In the socio-cultural aspect, the community develops a local early warning system through "titir" and a communication chain involving the community along the Panguluran watershed armed with traditional technology, as well as the mutual development of a public evacuation site in the form of multi-storey buildings, in addition to every family capable of building terraced houses . In addition, the community has the capacity to survive in saving economic assets by creating "plenggrongan" and planting calendar systems for crisis management. Diversification of plants such as planting bananas and sengon for daily use and annual savings when agricultural land was destroyed by flood.DOI: 10.17977/um022v4i22019p082